Pathogenesis of Kawasaki disease: the central role of TNF-αα. Issue 1 (February 2008) - Stringer, Elizabeth; Yeung, Rae SM
Kawasaki disease is the leading cause of multisystem vasculitis in childhood. The coronary arteries are targets of long-term inflammation and damage, making Kawasaki disease the leading cause of acquired heart disease in children from the developed world. The link between the systemic immune response seen in the acute phase of Kawasaki disease and subsequent damage to the coronary arteries is not clearly understood. Recent work points to TNF-αα and its downstream effector molecules as the key players in mediating coronary artery damage. In this article, we will review the evidence pointing to TNF-αα in the pathogenesis of disease and the implications for therapy.